Cadaver dissection study of the pectoral nerves for feasibility in brachial plexus injuries - M. Srijana; Srikanth R. (International Journal of Medical Research and Review, 2016)
Injury to upper trunk of Brachial Plexus is the most common injury pattern. Major functions affected those of supra scapular nerve (SSN), axillary nerve (AXN) and musculocutaneous nerve (MCN) which resulting dysfunction of elbow flexion shoulder abduction and internal rotation. Intra‐plexal nerve donors are more efficacious than extra‐plexal nerve donors and expendable.